In Nanaku: Local Knowledge of The Coastal Fishermen Community Taniwel Seram - Touwe Sem (EDP Sciences, 2021)
This paper wants to explain how Nanaku, as local knowledge of the coastal community in Taniwel sub-district, western Seram Regency had an important role in the marine activities. The purpose of the study was to explain the local knowledge of the community related to the skills and accuracy in marking natural phenomena related to marine activities. This study used descriptive qualitative methods, which included data collection, data reduction, data presentation, and drawing conclusions or verification. The results showed that Nanaku was passed down from generation to generation. Through this local knowledge, they can hold the process of making boats and fishing in the sea properly. This local knowledge was used as a natural marker and fishing guideline. Nanaku consisting of twelve fishing skills; nanaku moon, nanaku karti star, nanaku beluku star, nanaku scaly clouds, nanaku high and low tide, nanaku whirl wind, nanaku ocean currents, nanaku when river water overflows/ floods , nanaku seagulls lock, nanaku owl (boel), nanaku lunar eclipse, and nanaku lightning in Northeast at night. The conclusion showed that Nanaku still survives today and was not lost in the midst of technological developments. Nanaku became a basic knowledge for a fishing profession which contributed to the economic life of the coastal fishing communities of Taniwel Seram.